Depletion reveals role of bicarbonate in the photosynthetic electron transport chain of Limnospira maxima - Castillo, Leslie; Nicolaou, Stavroula; Gates, Colin (Frontiers in Plant Science, 2025)
Efficient photosynthetic light reactions require tight balancing of electrons and protons. In photosystem II, bicarbonate is coordinated to a non-heme iron positioned between the acceptor-side plastoquinones QA and QB, modulating electron transfer. The hypercarbonate-requiring filamentous cyanobacterium Limnospira maxima has had multiple bicarbonate functions on both acceptor and donor side of PSII determined by depletion. 77K spectrofluorometric investigation of phycobilin and chlorophyll excitation suggests the mild in vivo depletion method for bicarbonate results in loss of chlorophyll connectivity to the reaction center in PSII and dissociation of the phycobilisome due to proportional increase of fluorescence emission from allophycocyanin. Using chlorophyll fast repetition rate fluorometry, it was observed under bicarbonate depletion that oscillations were still present in a fraction of PSIIs, confirming the functionality of the water oxidizing complex remains in this fraction of centers. In these fractions of centers only one to two electrons are being released. QA- reoxidation kinetics indicate that loss of bicarbonate permits successful electron transfer to QB, forming semiquinone QB-. DCMU inhibition of the second electron transfer implies that, in bicarbonate-depleted L. maxima, electron transfer to QB affects proton delivery needed for plastoquinol formation, which suggests that this depletion targets the non-heme iron. Based on cytochrome b6f redox kinetics, depleted cells experience less intensity of oxidation and upon illumination cytochrome b and f are proportionally rapidly and intensely oxidized. P700 redox kinetics exhibit a delay feature in PSI as well as the expected delay of electron delivery to PSII, suggesting a further bicarbonate effect on PSI.